2011
DOI: 10.1590/s1516-35982011000400012
|View full text |Cite
|
Sign up to set email alerts
|

Levedura hidrolisada como fonte de nucleotídeos para leitões recém-desmamados

Abstract: Com este trabalho objetivou-se avaliar os efeitos de níveis de nucleotídeos em dietas para leitões recém-desmamados sobre o desempenho, a morfometria de órgãos e a histologia do epitélio intestinal. Foram utilizados 144 leitões desmamados aos 21 dias de idade e com peso médio inicial de 5,80 ± 0,16 kg em um experimento inteiramente ao acaso, com seis dietas, seis repetições por dieta e quatro animais por baia (unidade experimental). As dietas foram: Am (antimicrobiano) _ dieta basal com inclusão de 40 ppm de s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
1
4
0
13
Order By: Relevance
“…As to the visceral assessment, the smallest length of the small intestine (total and relative) may be related to the high incidence of watery diarrhea and villous atrophy that reduce the time for recovery and development of the intestinal epithelium (LALLÉS et al, 2004); although the rate of cell replication of the crypts is a response to tissues aggression, it is not a positive response of the development of the intestinal epithelium HAMPSON, 2003). Andrade et al (2011) found increased intestinal length with the use of colistin while evaluating different nucleotide sources, whereas Rizzo et al (2010) and Costa, Tse and Miyata (2007) observed a reduction in the intestinal length with the use of antibiotics in chickens and pigs, respectively, and attributed this response to an improvement in intestinal health of the animals, because an increase in intestinal length could result in greater energy expenditure and lower feed efficiency for the animal (GOMES et al, 2007). Comparing the average relative length of the small intestine reported in other studies, it was found that the results for this parameter in the present study were lower than those reported in other studies (0.516 μm versus 0.950 μm, according to Andrade et al (2011) and 0.720 µm, as noted by , thus demonstrating that there was some setback in the development of the small intestine for all treatments, with the COS treatment showing the lowest relative length.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As to the visceral assessment, the smallest length of the small intestine (total and relative) may be related to the high incidence of watery diarrhea and villous atrophy that reduce the time for recovery and development of the intestinal epithelium (LALLÉS et al, 2004); although the rate of cell replication of the crypts is a response to tissues aggression, it is not a positive response of the development of the intestinal epithelium HAMPSON, 2003). Andrade et al (2011) found increased intestinal length with the use of colistin while evaluating different nucleotide sources, whereas Rizzo et al (2010) and Costa, Tse and Miyata (2007) observed a reduction in the intestinal length with the use of antibiotics in chickens and pigs, respectively, and attributed this response to an improvement in intestinal health of the animals, because an increase in intestinal length could result in greater energy expenditure and lower feed efficiency for the animal (GOMES et al, 2007). Comparing the average relative length of the small intestine reported in other studies, it was found that the results for this parameter in the present study were lower than those reported in other studies (0.516 μm versus 0.950 μm, according to Andrade et al (2011) and 0.720 µm, as noted by , thus demonstrating that there was some setback in the development of the small intestine for all treatments, with the COS treatment showing the lowest relative length.…”
Section: Resultsmentioning
confidence: 99%
“…The fragments were cut into approximately 0.5 cm long samples, dehydrated in alcohol, diaphanized in xylol, and embedded in paraffin. Tissue sections, 5 µm thick, were obtained with American Optical microtome, and between one section and the subsequent one 30 sections were discarded (BERTOLETTO et al, 2008); four semi-seriated sections were arranged on one slide. The sections were stained with hematoxylin-eosin for histological assessment and with Alcian blue stain for goblet cell count.…”
Section: Description Of the Experimentsmentioning
confidence: 99%
“…Não foram observadas correlações entre estas variáveis e a utilização dos tratamentos com levedura (p>0,05). Andrade et al (2011), ao utilizar tratamento com antimicrobiano e diferentes níveis de nucleotídeos (0, 150, 300, 450, 600 ppm) na dieta de leitões, verificou que na dieta dos animais em que havia antibióticos houve maior comprimento do intestino delgado em relação aos demais tratamentos, sem afetar o peso dos demais órgãos e desempenho do animais. O peso do estômago não se diferenciou entre os tratamentos, concordando com Castillo et al (2004), que ao utilizar levedura desidratada (Saccharomyces cerevisae) como fonte proteica também não encontrou diferença significativa para peso relativo do estômago.…”
Section: Fasesunclassified
“…O peso do estômago não se diferenciou entre os tratamentos, concordando com Castillo et al (2004), que ao utilizar levedura desidratada (Saccharomyces cerevisae) como fonte proteica também não encontrou diferença significativa para peso relativo do estômago. Quanto ao baço, o peso relativo também não sofreu influência dos tratamentos, discordando de Andrade et al (2011), que verificou em seu estudo com leitões recém-desmamados, aumento linear do peso relativo deste órgão em relação aos níveis de nucleotídeos das dietas. Santos et al (2003) trabalhou com diferentes níveis de manose (0%, 0,02%, 0,10%) em substituição aos antibióticos na ração de suínos em fase de creche e observaram que os tratamentos não influenciaram nos pesos relativos e absolutos do baço, fígado e pâncreas.…”
Section: Fasesunclassified
“…Não foram encontradas diferenças (P>0,05) na ocorrência de diarreia nos leitões durante o período total de experimentação (Tabela 6). Estes resultados estão de acordo com estudos realizados em condições similares de criação com leitões recém-desmamados alimentados com dietas contendo antimicrobianos, prebióticos, probióticos ou fitoterápicos (COSTA et al, 2011;UTIYAMA et al, 2006). A baixa ocorrência de diarreia no período total de experimentação foi semelhante entre os tratamentos (P>0,05) e pode estar relacionada às condições de criação, tais como, dietas complexas, longo intervalo entre lotes, adequadas condições de higiene e baixo desafio sanitário aos leitões.…”
Section: Desempenho E Diarreiaunclassified